Appraisal of China's Response to the Outbreak of COVID-19 in Comparison With SARS - Li, Jiajia; Li, Shixue; Cao, Wuchun; Wang, Zhongli; Liang, Zhuohui; Fu, Wenhao; Zhao, Jinfeng (Frontiers in Public Health, 2021)
Coronavirus disease 2019 (COVID-19), which is caused by severe acute respiratory syndrome coronavirus 2, was first reported in Wuhan, China in December 2019, and has led to a worldwide pandemic. Although similar containment measures were implemented for COVID-19 to those used with severe acute respiratory syndrome (SARS), they were initiated at an earlier stage and on a larger scale, were more organized, and were more forceful. In light of lessons learned from SARS, the Chinese government acted aggressively in response to COVID-19, using a unified and effective commanding system, law-based and science-driven strategies, and coordinated deployment of medical resources. Additionally, the application of high-tech measures, traditional Chinese medicine, and hierarchical medical systems also played an important role in control measures. Despite the remarkable performance, the initial delay in response suggests that the coordination between public health and medical services, reserve and coordination of emergency materials, and capacity for disease control and prevention need to be strengthened.